Patient Satisfaction and Challenges of the Health Care Services of Negros Occidental Provincial Medical Clinic - Gerzon, M.D., Rowel A.; Salugsugan, John Clifford P. (Philippine Social Science Journal, 2020)
The Medical Clinic provides outpatient health services to the employees of the Provincial Government of Negros Occidental. Patient satisfaction gauges the quality of health care services. This study assessed the level of patient satisfaction on the health services and identified the challenges encountered by patients. Also, it compared the level of patient satisfaction in terms of their demographic profile. This descriptive-comparative design used a researcher-made survey questionnaire which was administered to 307 employees. The study revealed that the overall level of satisfaction was very high. A significant difference was found in the level of patient satisfaction when respondents were categorized according to sex and age. The most significant challenge encountered by patients was insufficient medicines and medical supplies. The findings were used as baseline data in designing a Clinic Manual of Procedures and Holistic Health Program for the Provincial Health Office.